2011
DOI: 10.1118/1.3576105
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel film dosimetry with nonuniformity correction

Abstract: Multichannel dosimetry with radiochromic film like Gafchromic EBT2 is shown to have significant advantages over single channel dosimetry. It is recommended that the dosimetry protocols described be implemented when using this radiochromic film to ensure the best data integrity and dosimetric accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
432
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(458 citation statements)
references
References 18 publications
5
432
0
4
Order By: Relevance
“…Because the response of EBT3 can vary within a sheet, as shown by Micke et al, a calibration curve based on net‐optical density (Δ OD ) was created 23. Films were scanned immediately prior to exposure and 24 hr after exposure using a flatbed transmission scanner (Epson Perfection V700, SEIKO Epson Corporation, Suwa, Japan) at 300 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…Because the response of EBT3 can vary within a sheet, as shown by Micke et al, a calibration curve based on net‐optical density (Δ OD ) was created 23. Films were scanned immediately prior to exposure and 24 hr after exposure using a flatbed transmission scanner (Epson Perfection V700, SEIKO Epson Corporation, Suwa, Japan) at 300 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…While the use of reflective mode for the film scanning under Bouchard's protocol is not in common use, reflective mode has been examined in previous papers 20 , 21 to produce comparable results to transmission mode (22) . While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect.…”
Section: Discussionmentioning
confidence: 99%
“…The sole result of the change in dose was a rescaling of the dose rate; no alteration to the MLC leaf positions, gantry speeds or treatment time was observed. There was no such limitation present in Ashland's FilmQA Pro due to its use of triple channel dosimetry and its “one scan” protocol (22) . Bouchard's protocol also is capable of a higher degree of accuracy (~1% compared to ~2% from FilmQA Pro), but the protocol is more labor intensive, requiring the average of multiple film scans as well as scanner inhomogeneity corrections.…”
Section: Discussionmentioning
confidence: 99%
“…The test fields (Table 2) were delivered to the EBT3 film which was positioned at 90 cm SSD with 10 cm buildup and 5 cm backscatter of Solid Water Model 457. The film was scanned using the single scan protocol (16) on an Epson Expression 10000 XL scanner (US Epson, Long Beach, CA) using the recommended scanning resolution of 72 dpi in a 48‐bit RGB format 16 , 17 , 18 . Glass was placed over the calibration and test film during scanning to minimize Newton's rings artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…Glass was placed over the calibration and test film during scanning to minimize Newton's rings artifacts. Lateral displacement of the film within the scanner can cause deterioration in the accuracy of the dose measured with greater deterioration the further the film is from the center of the scanner (17) . Deviations resulting from the lateral displacement were observed on film dose profiles from the ‘20×20’ test beam.…”
Section: Methodsmentioning
confidence: 99%